SYMBOLS OF HEROISM IN THE LITERATURE OF THE PEOPLES OF THE GREAT SILK ROAD (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article presents the specific features of the heroic image in the literature of the peoples of the Great Silk Road, mainly expressed through such qualities as courage, patriotism, intelligence, loyalty and struggle for justice. A comparative analysis is made of Alpomish in the epic poem "Alpomish" and Sun Ukun in the novel "Journey to the West".